EVALUASI SISTEM PENGENDALIAN INTERN TERHADAP PROSES PEMBERIAN KREDIT PADA PT. MANDIRI TUNAS FINANCE KOTA LUBUKLINGGAU - Dheo Rimbano (LPPM UNIVERSITAS BINA INSAN, 2016)
The formulation of the problem in this study is: how the internal control system of credit provision is applied to PT. Mandiri Tunas Finance. The purpose of the study was to find out the application of the internal control system to the lending process at PT. Mandiri Tunas Finance (MTF) Lubuklinggau City. the data collection technique used is observation while the data analysis technique uses qualitative methods. The results of the study indicate that the evaluation of the process of granting credit to PT. Mandiri Tunas Finance (MTF) of Lubuklinggau City both in terms of documents, organizational structure, authorization system, sound practices and competent human resources which includes procedures or standard operating procedures